CRISPR-Cas9 Genome Editing for Treatment of Atherogenic Dyslipidemia - Chadwick, Alexandra C. (Arterioscler Thromb Vasc Biol, 2017)
Although human genetics has resulted in the identification of novel lipid-related genes that can be targeted for the prevention of atherosclerotic vascular disease, medications targeting these genes or their protein products have short-term effects and require frequent administration during the course of the lifetime for maximal benefit. Genome-editing technologies, such as CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats-CRISPR–associated 9) have the potential to permanently alter genes in the body and produce long-term and even lifelong protection against atherosclerosis. In this review, we discuss recent advances in genome-editing technologies and early proof-of-concept studies of somatic in vivo genome editing in mice that highlight the potential of genome editing to target disease-related genes in patients, which would establish a novel therapeutic paradigm for atherosclerosis.